Letter To The Editor - Selin Engin (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
This letter is about Ayşe Nur Balcılar’s and Serkan Çınarlı’s study titled "Social Municipalism Applications in Turkey and Example of Bornova Municipality ", which is on pages 2020; 21(2): 122-156 of Sivas Cumhuriyet University Journal of Economics and Administrative Sciences.